Diversity and cultural competence in health care a systems approach - Dreachslin, Janice L. (Jossey-Bass, 2013)
"Written by three nationally known scholars and experts, Diversity, Inclusion, and Cultural Competence in Health Care: A Systems Approach is designed to provide upper division and graduate level health care students and professionals with a clear understanding of recent philosophies and processes undergirding diversity management, inclusion, and culturally competent care delivery as seen through the lens of current health care policy and practice. The textbook integrates strategic diversity management, self-reflective leadership and the personal change process, with culturally and linguistically appropriate care into a cohesive systems-oriented approach for health care professionals"--Provided by publisher.